Formative research for a community-based message-framing intervention. - Martinez, Josefa L; Latimer, Amy E; Rivers, Susan E; Salovey, Peter (American journal of health behavior, 2012)
To inform a community-based message framing intervention encouraging physical activity and fruit and vegetable consumption among medically underserved adults.
Keywords: Acculturation; Adult; Community Networks; Diet; Exercise; Female; Focus Groups; Health Behavior; Health Literacy; Hispanic Americans; Humans; Interviews as Topic; Male; Middle Aged; Persuasive Communication; Research; Risk Reduction Behavior; United States